2016
DOI: 10.2527/jas.2016-0392
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior of growing–finishing pigs reared under precision feeding strategies1

Abstract: The feeding behavior of growing-finishing pigs reared under precision feeding strategies was studied in 35 barrows and 35 females (average initial BW of 30.4 ± 2.2 kg) over 84 d. Five different feeding programs were evaluated, namely a conventional 3-phase program in which pigs were fed with a constant blend of diet A (high nutrient density) and diet B (low nutrient density) and 4 daily phase-feeding programs in which pigs were fed daily with a blend meeting 110, 100, 90, or 80% of the individual Lys requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 27 publications
6
45
0
5
Order By: Relevance
“…In the present experiment, feeding activity was predominantly diurnal. The proportions of feed consumed during the 0.01-8.00, 8.01-16.00, and 16.01-24.00 periods were 0.19, 0.42 and 0.39 of total daily intake, respectively, reflecting the influence of the circadian rhythm (Andretta et al, 2016). On average, each pig spent 57.8 min/d feeding, so that the mean individual daily occupation of the feeder was in the order of 0.48 (57.8 min/60 min × 12 pigs/24 h).…”
Section: General Patternmentioning
confidence: 95%
“…In the present experiment, feeding activity was predominantly diurnal. The proportions of feed consumed during the 0.01-8.00, 8.01-16.00, and 16.01-24.00 periods were 0.19, 0.42 and 0.39 of total daily intake, respectively, reflecting the influence of the circadian rhythm (Andretta et al, 2016). On average, each pig spent 57.8 min/d feeding, so that the mean individual daily occupation of the feeder was in the order of 0.48 (57.8 min/60 min × 12 pigs/24 h).…”
Section: General Patternmentioning
confidence: 95%
“…Lower BIW is associated with higher morbidity, different developmental patterns, and changes in body composition and homeostasis, due to prenatal programming through epigenetic changes (Gondret et al 2005b(Gondret et al , 2006Gonzalez-Bulnes et al 2016;Ji et al 2017). Within-litter BIW variation (BIWV) may be associated with a high variability in carcass and meat quality in the same feedlot, which affects profitability and the production of dry-cured products (Andretta et al 2016). Moreover, sex effects contribute to reducing feedlot homogeneity (Egea et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the diurnal influence was attributed to the cows eating more during the daytime than during the nighttime. Similarly, multiple recent studies using automatically collected data have identified diurnal feeding patterns in pigs (Fernández et al, 2011;Hoy et al, 2012;Andretta et al, 2016). Although it is intuitive to think BW of pigs might also follow a diurnal pattern, no previous research appears to have verified that assumption.…”
Section: Introductionmentioning
confidence: 99%